Review of partial analitical management models in capability-based systems - Yasenko, Serhii; Tkach, Ivan (Social Development and Security, 2023)
Purpose: is to demonstrate the coherence of a set of models for management in systems based on capabilities within the framework of known theories (theory of systems, theory of subjective analysis).Method: the research used elements of graph theory, probability theory, optimality theory, scenario approach, success model and the concept of “active system” from the theory of subjective analysis.The results of the study: the article formulated a problematic situation regarding the development of the country's defense system; the task of reforming the defense system is formulated as measures to transfer the system from a state with unsatisfactory indicators to a state with satisfactory indicators; a formal notation of capacity estimation through conditional probability decomposition of total capacity is provided; a description of the formal definition of tasks within typical defense planning scenarios is given; the relationship between known models of management in systems based on capabilities within known theories (theory of systems, theory of subjective analysis) is shown.Theoretical implications: the article showed that management models based on capabilities are a harmonious part of classical systems theory models.Practical implications: the results of the work allow a significant amount of qualitative research in the direction of defense planning based on capabilities to be presented using formal analysis tools.Future research: the article considered the presentation of a part of management tasks based on capabilities based on only a small part of the most well-known classical models of systems theory. Further development of this direction of research is related to the formalization of practical examples of planning and assessment of capabilities using the proposed models.Papertype: descriptive, methodical.